Novel data according Will Roger`s phenomenon in stomach cancer patients - Dubinina, V. G.; Lukjanchuk, O. V.; Lurin, A. G.; Маshukov A. A.; Bilenko, A. A.; Zgura, A. N.; Raciborsky, D. V.; Merlich, S. V.; Shilin, I. V. (Journal of Education, Health and Sport, 2016)
Dubinina V. G., Lukjanchuk О. V., Lurin A. G., Маshukov А. А., Bilenko А. А., Zgura A. N., Raciborsky D. V., Merlich S. V., Shilin I. V. Novel data according will roger`s phenomenon in stomach cancer patients. Journal of Education, Health and Sport. 2016;6(6):185-206. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55178 http://ojs.ukw.edu.pl/index.php/johs/article/view/3570 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. Novel data according Will Roger`s phenomenon in stomach cancer patients Dubinina V. G.1, Lukjanchuk О. V.1,2, Lurin A. G.2, Маshukov А. А.1,2, Bilenko А. А.2, Zgura A. N.2, Raciborsky D. V.2, Merlich S. V.2, Shilin I. V.2 Odessa national medical university1 Odessa regional oncologic center2 Acknowledgments: Supported by the Oncological Department of Odessa Regional Pathology Service. Summary Mostly Will Roger`s phenomenon means existence of so-called "jumping" or "jumping over the stages" regional metastases in the stomach cancer patients. N1 in the 6th edition means 16 regional lymph nodes involvement, while the N1 seventh edition – only 1-2 of regional lymph nodes involvement. This means that T1N1Mo 6th and T1N1Mo 7th - not quite the same, and the survival of the two groups will be different. The study, made on the abdominal oncosurgical department of Odessa Regional Oncology Center, included 188 patients operated for gastric cancer in the period 2007-2011. The study included only radically treated patients. Comparison of survival in patients with gastric cancer between 6th revision groups of 7th has been reviewed. The classification mission is to provide differences in the survival rates between the groups. Regression multivariate Cox analysis showed that 7th UICC classification showed different capability of stratifying survival groups of UICC N classification (P 0.01). Key words: extended lymphatic dissection, TNM classification, Will Roger`s phenomenon, stomach cancer.